Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.3390/vaccines8010133
|View full text |Cite
|
Sign up to set email alerts
|

Comparisons of Antibody Populations in Different Pre-Fusion F VLP-Immunized Cotton Rat Dams and Their Offspring

Abstract: Respiratory syncytial virus (RSV) infection poses a significant risk for infants. Since the direct vaccination of infants is problematic, maternal vaccination may provide a safer, more effective approach to their protection. In the cotton rat (CR) model, we have compared the immunization of pregnant CR dams with virus-like particles assembled with the prototype mutation stabilized pre-fusion F protein, DS-Cav1, as well two alternative mutation stabilized pre-fusion proteins (UC-2 F, UC-3 F) and showed that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 51 publications
0
12
0
Order By: Relevance
“…In these studies, we have used RSV-primed animals since most if not all normal human populations have been previously infected with RSV. We have reported that immunization of RSVprimed dams during pregnancy with pre-F VLPs resulted in robust protection of offspring from RSV challenge with no evidence of pathology [29][30][31]. Here we describe the durability of these protective responses in dams after a single immunization and compare the degree of protection these dams can transfer to their offspring in two consecutive litters.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…In these studies, we have used RSV-primed animals since most if not all normal human populations have been previously infected with RSV. We have reported that immunization of RSVprimed dams during pregnancy with pre-F VLPs resulted in robust protection of offspring from RSV challenge with no evidence of pathology [29][30][31]. Here we describe the durability of these protective responses in dams after a single immunization and compare the degree of protection these dams can transfer to their offspring in two consecutive litters.…”
Section: Introductionmentioning
confidence: 89%
“…McLellan et al identified mutations in the RSV F protein (DS-Cav1 mutant) that stabilize the pre-fusion conformation, and this prototype pre-fusion F protein is now widely used in many vaccine candidates in different stages of development [5]. Subsequently, others have reported different F protein mutations that are stabilizing [28], one of which, UC-3 F, induces higher neutralizing antibody (NAb) titers than the widely-used form, DS-Cav1 F [28,29]. We have assembled VLPs containing the DS-Cav1 or the UC-3 F pre-fusion RSV F proteins along with the RSV G attachment protein and have established UC-3 F VLP superiority over DS-Cav1 F as well as post-F protein, or wildtype F protein containing VLPs in inducing NAbs in both mice and cotton rats [28,30].…”
Section: Introductionmentioning
confidence: 99%
“…The copyright holder for this preprint this version posted September 13, 2022. ; https://doi.org/10.1101/2022.09.12.507712 doi: bioRxiv preprint and G protein ectodomains fused to the transmembrane and cytoplasmic domains of the NDV F and HN, respectively, for efficient assembly into the VLPs (19)(20)(21)(22). We have shown that these VLPs induce both anti-RSV F and anti-RSV G antibodies and good protective responses in the cotton rat model commonly used in RSV studies (19)(20)(21)(22)(23).…”
Section: Introductionmentioning
confidence: 99%
“…In these studies, we have used RSV-primed animals in order to mimic normal human populations, most of which have been previously infected with RSV. We have reported that immunization of RSV-primed dams during pregnancy with pre-F VLPs resulted in robust protection of offspring from RSV challenge with no evidence of pathology (29)(30)(31). Here we describe the durability of these protective responses in dams after a single immunization and compare the degree of protection these dams can transfer to their offspring in two consecutive litters.…”
Section: Introductionmentioning
confidence: 99%